EVALUASI CARA PENGGUNAAN INJEKSI INSULIN PEN PADA PENDERITA DIABETES MELLITUS DI RSUD ULIN BANJARMASIN - Atmaja, Meta Adiwinata; Diani, Noor; Rahmayanti, Devi (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2017)
Diabetes mellitus is one of a disease that can not be cured but can be control with insulintreatment. However, in providing treatment of insulin injections also with right dose, right lane,right time and right location. This study aims to Assessed the use of insulin pen injection ondiabetes mellitus patients in hospital Ulin Banjarmasin. This study was used a descriptive methodto described the important events that occurred. Respondents were 30 people. The samplingtechnique used accidental sampling. Study scheduled in December 2016-January 2017. Theinstruments used were a questionnaire on demographic and format of assessment to evaluate howto use insulin pen injection. The results showed the data of 20 (66.7%) of respondents werecorrected and in the proper used of insulin injection pen and 10 (33.3%) of respondents were notprecised and corrected in using insulin pen injection. It should be carried out to evaluate theprogram on how to use Insulin pen injection so as to optimised the use of the application insulininjection pen that is good and right.